ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN PADA TOKO PLASTIK RIZKA DI TENGGARONG - Yanti, Meli; Wijayanti, Silvana; Hendra (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2025)
Customer satisfaction is an important thing in business place satisfaction becauseif customers feel dissatisfied it will make consumers disloyal to that place ofbusiness. The writing of this final assignment uses five dimensions which includethe dimensions of direct evidence (tangibility), reliability, responsiveness,assurance and empathy to determine the level of consumer satisfaction with theservice at the Risca Plastic Shop. The problems that occur in this business placeare regarding customer satisfaction in the aspects of cleanliness and tidiness, thelocation of the business place and employees in providing orders according toconsumer wishes. This can be seen from the interview results which show that thereare still respondents who feel quite satisfied. The author suggests that businessowners pay more attention to the cleanliness of their business premises by creatinga special warehouse to store supplies and making signboards to make it easier forconsumers to find their business premises. And create a policy to increaseemployees so they don't ask questions when handling their work.Keywords: Consumer Satisfaction, Service Quality and Buying Decision